Water Resources Development in Nepal: Myths and Realities - Upadhyay, Surya Nath; Gaudel, Prakash (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Despite the ‘immense’ water resources available, Nepal has not been able to transform this abundance of water resources into desired economic growth and societal welfare. This paper attempts to analyze the reasons for such incessant challenges that loom over water resources development in Nepal. This paper finds that it is not the resource that limits the development of water resources, but the approaches and wishes that are framed on the foundation of persistent myths. Analyzing those myths, this paper highlights the realities in water resources management of Nepal, and suggests that without dismantling the existing myths, the sustainable development of water resources seems limited. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018